The Linguistic Review (De Gruyter Mouton, 1981)
The Linguistic Review publishes high-quality papers in syntax, semantics, phonology and morphology within a framework of Generative Grammar and related disciplines, as well as critical discussions of theoretical linguistics as a branch of cognitive psychology. The journal welcomes reviews of important new monographs in these areas, dissertation abstracts and letters to the editor.